Enzymes of cysteine synthesis show extensive and conserved modifications patterns that include Nα-terminal acetylation - Wirtz, Markus; Heeg, Corinna; Samami, Arman Allboje; Ruppert, Thomas; Hell, Rüdiger (Amino acids, 2010)
Biosynthesis of cysteine is a two-step process in higher plants subsequently catalyzed by serine acetyltransferase (SAT) and O-acetylserine (thiol) lyase (OAS-TL) which are present in cytosol, plastids and mitochondria. Recently, the distribution of SAT and OAS-TL in these subcellular compartments was shown to be crucial for efficient cysteine synthesis in Arabidopsis thaliana. In this study, the abundances of OAS-TLs were quantified independently by immunological detection in crude protein extracts and by SAT affinity purification (SAP) of OAS-TL. OAS-TL A and B were evidenced to be the most abundant isoforms in all analyzed tissues, which is consistent with micro array-based transcript analyses. Application of SAP to Arabidopsis revealed significant modification of the major OAS-TL isoforms present in cytosol, plastids and mitochondria into up to seven subspecies. Specific OAS-TL isoforms were found to be differentially modified in the leaves, roots, stem and cell culture. Sulphur deficiency did not alter modification of OAS-TL proteins purified from cell culture that showed the highest complexity of OAS-TL modifications. However, the pattern of OAS-TL modification was found to be stable within an analyzed tissue, pointing not only to a high reproducibility of SAP but likely biological significance of each subspecies. The most abundant OAS-TL subspecies in cytosol and plastids were subject of N-terminal processing followed by acetylation of the newly originated N-terminus. The mode of Nα-terminal acetylation of OAS-TL and its possible biological function are discussed.